The Internationalization of Small Professional Service Firms: An Organizational Learning Perspective - Laperrière, Anika (Université d'Ottawa / University of Ottawa, 2013)
The purpose of this study is to examine how the internationalization process in small firms impacts their resource base renewal. The relationships between organizational learning, dynamic capabilities, operational capabilities and resources are empirically examined to determine the impact of internationalization on changes to the firm’s resource base. The empirical analysis follows a multiple case study research methodology and is based on in depth case studies of four internationalized professional service firms in Ontario. Cases include born-global and born-again global firms, exemplifying both location-based and knowledge-based services. The study finds evidence supporting the relationships between internationalization, organizational learning and planned change via dynamic capabilities, as well as internationalization, organizational learning and ad hoc problem solving. Findings also suggest that the firms’ repetitive use of ad hoc problem solving when faced with similar situations leads to the creation of dynamic capabilities. This research adds to the existing body of literature on services, international entrepreneurship and strategy by responding to a call for empirical examination of organizational learning within the RBV and DC constructs. Furthermore, it also applies a novel theoretical framework with which to examine the impact of small firm internationalization and their strategic renewal. By doing so, this thesis extends the RBV and DC perspectives to small service firms. Findings demonstrate a need to further continue this research path to gain greater understanding of the change processes that occur during the evolution of the firm’s resource base, as pertains to small knowledge-intensive service firms.
Keywords: Internationalization; Entrepreneurship; Organizational Learning; Small Firms; Resource-based View; Dynamic Capabilities; Qualitative